Can SMEs survive natural disasters? Eva Marie Arts and Crafts versus Typhoon Yolanda - Mendoza, Ronald U (Archīum Ateneo, 2018)
Promoting more resilient firms and production chains could be the key to much more resilient communities who remain in shock prone areas. Otherwise, shock-upon-shock will produce an immiserizing effect, notably among the smallest and most vulnerable firms. The experience of small and medium scale enterprises and their corresponding value chains affected by Typhoon Yolanda (also known as Typhoon Haiyan) offers important insights here. Public sector and donor support for disaster- and crisis-hit communities is critical; but it is only when firms get back up that the community is able to recover fully. Crises even offer opportunities for expansion and innovation for those firms that are most resilient and are able to boost their competitiveness after crises. Nevertheless, not all firms are able to seize opportunities during crises. These types of shocks have the potential to further increase the productivity divide between relatively smaller and larger firms. All these factors appear cogent in the case of Eva Marie Arts and Crafts, as it recovered from Typhoon Yolanda. Using data gathered through key informant interviews and focus group discussions with the relevant persons in the production chain of the firm, this case study reveals how the coherence across emergency aid and resilience building policy interventions is critical. It also highlights the necessity of knowing the language and circumstance of the locals, the human spirit of resilience, and the importance of supplying to businesses similar aid offered to individuals and households.